Mekanisme Pengaturan Dana Bantuan Korban Sebagai Alternatif Pemenuhan Restitusi Anak Korban Kekerasan Seksual - Abdillah, Ana; Setyorini, Erny Herlin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the urgency of regulating the victim assistance fund mechanism as an alternative to fulfilling restitution for child victims of sexual violence. The implementation of restitution still faces various obstacles, such as problems in submitting applications, calculating restitution that takes a long time, coordination in the implementation of asset confiscation, and structural obstacles in the implementation of asset auction procedures that ultimately hinder the fulfillment of victim rights. This study uses a normative legal method to analyze the relationship between legal principles and norms, and to compile prescriptive legal arguments. The data used include the Child Protection Law, the Sexual Violence Crime Law, as well as interviews with legal practitioners, service providers, and victims of sexual violence. The regulation of the victim assistance fund mechanism needs to be regulated in more detail in a Government Regulation (PP), which includes funding sources, allocations, and utilization of funds for compensation for underpayment of restitution. In addition, non-tax revenues (PNPB) from financial criminal sanctions can also support victim assistance funds.